THE EFFECT PERCEIVED OF SERVICE QUALITY, PERCEIVED OF WEBSITE QUALITY, AND PERCEIVED OF WEBSITE REPUTATION ON PURCHASE INTENTION: THE MEDIATION ROLE OF TRUST IN ONLINE SHOPPING - Dhimas Ramadhani Utama; Muhammad Ali Fikri; Poppy Laksita Rini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of perceived of service quality, perceived of website quality, and perceived of website reputation on purchase intention through the mediating role of trust in online shopping. This research uses a quantitative method with Smart PLS software. A variable measurement scale is carried out using a likert scale. The sample in this study were university students and the general public with an age range of 17-56 years who had used the website of the e-commerce application. Dissemination of the questionnaire using an online questionnaire link. A total of 103 tabulations of questionnaires were collected and analyzed successfully. The object of analysis in this study is a website or online shopping service. The analytical method used is the validity and reliability test, coefficient of determination test (adjusted r-square), and hypothesis testing. The results of this study prove that the perceived of service quality, perceived of website quality, perceived of website reputation has an effect on trust and purchase intention. Trust has a mediating role in the bond between perceived of service quality, perceived of website quality, and perceived of website reputation on purchase intention